Flavonoids and Triterpene of Ficus benghalensis - Elgindi, M.R. (Asian Journal of Chemistry, 2010)
5,6,7,3´,5´-Pentamethoxy-4´-prenyloxyflavone (1), rutin, quercetin and 3-acetyl ursa-14:15-en-16-one (2) were obtained from the leaves of Ficus benghalensis L (Moraceae). Their structures were determined on the basis of spectral data.